2011
DOI: 10.1073/pnas.1111415108
|View full text |Cite
|
Sign up to set email alerts
|

Fungal recognition is mediated by the association of dectin-1 and galectin-3 in macrophages

Abstract: Dectin-1, the major β-glucan receptor in leukocytes, triggers an effective immune response upon fungal recognition. Here we use sortase-mediated transpeptidation, a technique that allows placement of a variety of probes on a polypeptide backbone, to monitor the behavior of labeled functional dectin-1 in live cells with and without fungal challenge. Installation of probes on dectin-1 by sortagging permitted highly specific visualization of functional protein on the cell surface and its subsequent internalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 33 publications
2
115
0
Order By: Relevance
“…108 Interestingly, Galectin-3 also works in association with Dectin-1 on macrophages. 135 When macrophages expressing Dectin-1 are exposed to C. albicans mutants with increased exposure of b-glucan, the loss of Galectin-3 dramatically accentuates the failure to trigger an appropriate TNF-a response. 135 Moreover, the collaboration in immune response may also involve other cell receptors, such as peroxisome proliferator-activated receptor (PPAR)-g and CD44.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…108 Interestingly, Galectin-3 also works in association with Dectin-1 on macrophages. 135 When macrophages expressing Dectin-1 are exposed to C. albicans mutants with increased exposure of b-glucan, the loss of Galectin-3 dramatically accentuates the failure to trigger an appropriate TNF-a response. 135 Moreover, the collaboration in immune response may also involve other cell receptors, such as peroxisome proliferator-activated receptor (PPAR)-g and CD44.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
“…135 When macrophages expressing Dectin-1 are exposed to C. albicans mutants with increased exposure of b-glucan, the loss of Galectin-3 dramatically accentuates the failure to trigger an appropriate TNF-a response. 135 Moreover, the collaboration in immune response may also involve other cell receptors, such as peroxisome proliferator-activated receptor (PPAR)-g and CD44. PPAR-g is expressed in various immune cells and acts as a transcriptional repressor to inhibit the transcription of many proinflammatory cytokines.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
“…Gal-3 has been shown to interact with dectin-1 and TLR-2. 77,78 Previous studies using knockout mice have demonstrated that TGF-b1 and IL-6 fuel Th17 differentiation, while IL-23 facilitates the differentiation and sustains the Th17 cells. [79][80][81] IL-17A acts on a variety of cell types to promote inflammation 82 and helps eradicate extracellular pathogens.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…6,7 This immune receptor has been shown to associate with dectin-1, that specifically recognizes fungal b-1,3-glucan, to mediate fungal uptake, although galectin-3 is not essential for this process, working together in the proinflammatory response of macrophages. 18 Interestingly, dectin-1 mediates the increased binding and phagocytosis of cek1 mutants due to its enhanced cell wall glucan exposure, and the activation of intracellular signaling pathways of human dendritic cells and macrophages. 43 The observation of galectin-3 surrounding cek1 yeast cells during their interaction with macrophages, especially at early time points, suggest a role for both dectin-1 and galectin-3 in the increased recognition and phagocytosis of this mutant.…”
Section: Discussionmentioning
confidence: 99%